Green Synthesis of Silver Nanoparticles Using Ocimum tenuiflorum Leaf Extract and its Antimicrobial Activity against Certain Pathogens: Life Sciences-Microbiology for Health Care - Pal Nidhi; Shweta Agrawal (International Journal of Life Science and Pharma Research, 2022)
Nanoparticles (NPs) are particles less than 100 nm in size. Silver nanoparticles have many important chemical and biological applications. These applications drag the attention of researchers for the production of silver nanoparticles. The objective of the study is to synthesize silver nanoparticles from the green method without using any hazardous chemicals. In the present study, Ocimum tenuiflorum (Tulsi) leaf extract was used to synthesize silver nanoparticles (Ag-NPs) from silver nitrate. Moreover, Tulsi leaf extract was also exploited, both traditionally and commercially, for their antibacterial potential which is essential oil components. The synthesis of Ag-NPs was visually deduced by a change in colour from light yellow to reddish-brown. UV-Visible Spectrometry, X-ray diffraction (XRD), and Transmission Electron Microscopic (TEM) analysis were then used to characterize synthesized nanoparticles. This study also determined the effect of temperature and effect of silver nitrate concentration on nanoparticle synthesis. Synthesized silver nanoparticles showed absorbance ‘peaks’ at 420 nm with UV-visible spectrometry. X-ray diffraction studies showed that the synthesized silver nanoparticles were crystalline. The mean crystallite size was estimated using the Debye-Scherrer equation. However, TEM showed that silver nanoparticles have spherical (40 nm) shape with a narrow size distribution. These synthesized nanoparticles were used to evaluate antimicrobial activity against the most common pathogens of nosocomial infections, MRSA, E. coli, Salmonella typhi, and Klebsiella pneumoniae (ESBL). O. tenuiflorum extract showed strong potential for the synthesis of silver nanoparticles from silver nitrate and the synthesized silver nanoparticles had efficient antimicrobial properties against different pathogens including drug-resistant pathogens in vitro. These synthesized nanoparticles showed maximum ‘zones’ of inhibition against MRSA among these four organisms.